STUDY OF CONTROL OF GEOMORPHOLOGY AND BASE STONE ON LATERITE NICKEL DEPOSITS IN THE TAPUNOPAKA REGION OF NORTH KONAWE, SOUTHEAST SULAWESI - Dandi Nurshafara, Ifan
Sulawesi is one of the islands that has rich reserves of nickel (Ni) laterite ore in Indonesia. Nickel is used for many purposes including in industry, for example, Ni is a raw material for batteries in the electric car industry. The production of electric cars continues to increase, causing the demand for nickel to also increase. So to meet these needs, a detailed study of nickel laterite deposits is needed to increase the productivity of laterite Ni mining. The enrichment of Ni in Ni-laterite deposits is controlled by several factors, for example, the morphology and character of the bedrock. Therefore, this study discusses the geomorphological and bedrock control factors for Ni content in Ni-laterite deposits in the Tapunopaka area, North Konawe, Southeast Sulawesi which is included in the IUP PT Antam Tbk. The data used consists of 2 types, namely primary and secondary data. Primary data consisted of outcrop descriptions, geomorphological observations, and rock samples totaling 10 samples. while the secondary data consisted of DEMNAS data, geological maps of Lasusua-Kendari sheets, and assay data from 35 drill points consisting of (drill descriptions, depth intervals, and XRF data analysis). The method used is the observation of rock samples, petrographic descriptions, and geochemical analysis of the bedrock to determine the characteristics of the bedrock in the study area. Meanwhile, geomorphological analysis was carried out by using geomorphological observation methods in the field and analysis using secondary data to determine the morphology of the research area. Based on the analysis of geochemical data at each drill point, there are 2 types of Ni laterite in the study area, namely the type of oxide and the type of silica hydrate-Mg. This type of oxide is characterized by the enrichment of Ni in the limonite layer and Ni is associated with oxide and hydroxide minerals such as goethite. While the hydrate-Mg silica is characterized by the content of Ni enriched in the saprolite layer and Ni is associated with hydrate-Mg silicate minerals such as garnierite. Based on petrographic observations, dunite rocks are dominated by olivine minerals followed by pyroxene, serpentine and opaque minerals, while harzburgite rocks are dominated by pyroxene and olivine minerals followed by serpentine minerals and opaque minerals. In the harzburgite rock found in several v outcrops that show an intense level of serpentinization, macroscopically the rock appears to be dominated by serpentine minerals and iron oxides. Based on observations in the research area and the results of the calculation of the slope percentage, the research area consists of 3 types of geomorphology, namely hills with gentle slopes, hilly morphology with steep slopes, and morphology of alluvial deposits. The topography of the research area based on the slope is divided into flat slopes, light slopes, moderate slopes, and ridges. Based on the relationship between topography and the lateritization process, areas with gentle slopes have a more intensive level of lateritization than those with steeper slopes. The degree of lateritization affects the thickness of the laterite formed. In areas with flat slope topography and ridges that have relatively thick saprolite and limonite thicknesses, the presence of rivers and lineaments also affects the thickness of the limonite and saprolite layers. The results of the analysis carried out, Ni has high levels in harzburgite rocks which are strongly serpentinized in flat to slightly sloping topography. The thickness of saprolite and limonite is positively correlated with the Ni content, the thicker the laterite the higher the Ni content. Laterite thickness is also related to the type of Ni laterite. Thick limonite tends to have Ni oxide type laterite, while thick saprolite tends to have a hydrous Ni-Mg silicate type laterite.